2008
DOI: 10.1007/s11431-008-0024-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of influencing factors of hot streaks migration in high pressure stage of a vaneless counter-rotating turbine

Abstract: Three-dimensional, viscous, and unsteady CFD simulations have been performed in order to reveal the influencing factors of hot streaks migration in high pressure stage of a vaneless counter-rotating turbine. Based on the numerical results, the comparison between the case with inlet hot streaks and case without inlet hot streaks is carried out, which shows that the effect of inlet hot streaks on the load distributions of high pressure turbine airfoils is not notable and the airfoil load distributions are direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…In the previous work [3], iterations between airfoil blading and numerical analysis of 3D steady viscous flow were used in the designing process to solve the problem, and the final blade-to-blade passage was an equivalent convergentdivergent passage. Numerical simulation and experiment results [3,[5][6][7] showed that the designed blade was usable and far from perfect. The problem is that the iteration between airfoil blading and 3D calculations is not easy to put into practice, because it needs the designer to do a lot of iteration work, but even though it still lacks accuracy.…”
Section: Methods On Choosing Exit-to-throat Width Ratio For 3d Transonmentioning
confidence: 99%
See 2 more Smart Citations
“…In the previous work [3], iterations between airfoil blading and numerical analysis of 3D steady viscous flow were used in the designing process to solve the problem, and the final blade-to-blade passage was an equivalent convergentdivergent passage. Numerical simulation and experiment results [3,[5][6][7] showed that the designed blade was usable and far from perfect. The problem is that the iteration between airfoil blading and 3D calculations is not easy to put into practice, because it needs the designer to do a lot of iteration work, but even though it still lacks accuracy.…”
Section: Methods On Choosing Exit-to-throat Width Ratio For 3d Transonmentioning
confidence: 99%
“…As a result, convergent-divergent shape was adopted in the HPT rotor design [3]. Numerical simulation and experiment results [3,[5][6][7] showed that the designed blade could be used but it was far from perfect. The problem is that it requires the designer to do a lot of iteration work between airfoil blading and 3D calculations until the final blade is got.…”
Section: Purpose Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…To control the high-temperature, a cooling system has to be used. Optimum design of the cooling system requires the knowledge of migration characteristics of the hot jet and of parallel air flow [3]. There have been many studies regarding impingement of jets on an endplate [4] [5].…”
Section: Introductionmentioning
confidence: 99%
“…It is obvious that the VCRT will be widely adopted in real aero-engines in the future. From the 1950s, counter-rotating turbines have been carefully investigated [1][2][3][4][5][6][7][8] . Researchers focus on aerodynamic design of CRT, flow field analysis in CRT, and so on.…”
mentioning
confidence: 99%